Canadian Public Health Laboratory Network national syphilis in-laboratory serological testing recommendations - Morshed, Muhammad; Vallée, Maud; Zhou, Hong Yuan; Hasso, Maan; Stein, Derek; Tran, Vanessa; Regmi, Ayushi; Singh, Ameeta E; Hayden, Kristy; Jindal, Sapan; Hatchette, Todd F (Journal of the Association of Medical Microbiology and Infectious Disease Canada = Journal officiel de l'Association pour la microbiologie médicale et l'infectiologie Canada, 2025)
Syphilis, caused by the bacterium Treponema pallidum, is a centuries-old sexually transmitted disease that continues to be a significant global health concern. Despite the efficacy of penicillin the disease has seen a resurgence worldwide, including in Canada. In 2022, Canada reported 13,953 cases of infectious syphilis, representing a 109% increase since 2018, and 117 cases of congenital syphilis, a staggering 599% increase. Historically, gay and bisexual men who have sex with men have been predominantly affected; however, recent years have seen a significant rise in female cases, contributing to the increase in congenital syphilis. Syphilis diagnosis is complex, requiring specialized expertise. The Canadian Public Health Laboratory Network last updated its laboratory diagnosis guidelines in 2015. Given the advancements in diagnostic techniques and the pressing need for updated guidance, this document provides an overview of the syphilis-causing pathogen T. pallidum, its transmission, pathogenesis, and clinical manifestations. It also reviews the epidemiology of syphilis, highlighting recent trends in Canada, and discusses current and emerging serological laboratory diagnostic techniques. This updated guidance aims to equip health care professionals with the latest knowledge and recommended testing algorithms to accurately diagnose and manage syphilis, ultimately helping to address the rising rates of this disease and improve public health outcomes in Canada. La syphilis, causée par la bactérie Treponema pallidum, est une infection transmissible sexuellement qui existe depuis des centaines d'années et qui continue d’être un important problème de santé mondial. Malgré l'efficacité de la pénicilline, la maladie est en résurgence dans le monde, y compris au Canada. En 2022, le Canada a déclaré 13 953 cas de syphilis infectieuse, soit une augmentation de 109 % depuis 2018, et 117 cas de syphilis congénitale, soit une hausse ahurissante de 599 %. Par le passé, les hommes homosexuels et les hommes bisexuels qui ont des relations sexuelles avec des hommes étaient majoritairement touchés, mais ces dernières années, le nombre de cas de sexe féminin a considérablement augmenté, ce qui contribue à l'accroissement des cas de syphilis congénitale. Le diagnostic de syphilis est complexe et nécessite des compétences spécialisées. En 2015, le Réseau des laboratoires de santé publique du Canada a mis à jour ses directives pour le diagnostic en laboratoire. En réponse à la progression des techniques diagnostiques et au besoin pressant de directives plus à jour, le présent document fournit un aperçu de l'agent pathogène T. pallidum responsable de la syphilis, de sa transmission, de sa pathogenèse et de ses manifestations cliniques. Il passe également en revue l’épidémiologie de la syphilis, qui fait ressortir les tendances récentes au Canada, et aborde les techniques sérologiques actuelles et émergentes pour poser un diagnostic en laboratoire. Ces directives actualisées visent à transmettre aux professionnels de la santé les connaissances les plus récentes et les algorithmes de tests recommandés pour diagnostiquer et traiter la syphilis avec précision, afin d'ainsi contribuer à juguler les taux croissants de cette infection et à améliorer les résultats sanitaires au Canada.